An analysis of the daily changes in US Treasury security yields - Tanweer Akram; Anupam Das (Levy Economics Institute of Bard College, 2019)
This paper analyzes the dynamics of long-term US Treasury security yields from a Keynesian perspective using daily data. Keynes held that the short-term interest rate is the main driver of the long-term interest rate. In this paper, the daily changes in long-term Treasury security yields are empirically modeled as a function of the daily changes in the short-term interest rate and other important financial variables to test Keynes's hypothesis. The use of daily data provides a long time series. It enables the extension of earlier Keynesian models of Treasury security yields that relied on quarterly and monthly data. Models based on higher-frequency daily data from financial markets-such as the ones presented in this paper-can be valuable to investors, financial analysts, and policymakers because they make it possible for a real-time fundamental assessment of the daily changes in long-term Treasury security yields based on a wide range of financial variables from a Keynesian perspective. The empirical findings of this paper support Keynes's view by showing that the daily changes in the short-term interest rate are the main driver of the daily changes in the long-term interest rate on Treasury securities. Other financial variables, such as the daily changes in implied volatility of equity prices and the daily changes in the exchange rate, are found to have some influence on Treasury yields.
Keywords: E43; E50; E60; G10; G12; 330; Treasury Securities; Government Bond Yields; Long-Term Interest Rate; Short-Term Interest Rate; Monetary Policy; US Government Debt